2003
DOI: 10.1021/ic034257k
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Zn and Pd Tetranaphthaloporphyrins

Abstract: Zn and Pd complexes of meso-tetraphenyltetranaphthaloporphyrins (Ph(4)TNP) exhibit strong infrared absorption bands and luminesce in solutions at room temperature. S1 --> S0 fluorescence (lambda(max) = 732 nm, phi = 5.3%) is the predominant emission in the case of ZnPh(4)TNP (1). This emission is in part due to the delayed fluorescence (phi = 1.1%). Phosphorescence (T1 --> S0) of 1 (lambda(max) = 973 nm) is very weak (phi = 0.04%) and occurs with lifetime of about 440 micros in deoxygenated DMF. In the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Palladium(II) and platinum(II) complexes with benzo- [188] and naphthoporhyrins [73, 188, 191] represent another group of the NIR oxygen indicators. These dyes belong to the class of π-extended porphyrins which are characterized by an extended aromatic fragment fused on the porphyrin core; this feature is responsible for the bathochromic shift of the absorption and emission bands.…”
Section: Luminescence-based Indicatorsmentioning
confidence: 99%
“…Palladium(II) and platinum(II) complexes with benzo- [188] and naphthoporhyrins [73, 188, 191] represent another group of the NIR oxygen indicators. These dyes belong to the class of π-extended porphyrins which are characterized by an extended aromatic fragment fused on the porphyrin core; this feature is responsible for the bathochromic shift of the absorption and emission bands.…”
Section: Luminescence-based Indicatorsmentioning
confidence: 99%
“…[33][34][35][36][37][38] ESR characterization ESR spectra for the tetrabutano and tetrabenzo derivatives of Cu(II) at 110 K in CH 2 Cl 2 are illustrated in Fig. has a relatively high intensity due to the increased conjugation between the four fused benzo groups and the macrocycle of the compounds.…”
Section: Synthesis and Uv-vis Spectramentioning
confidence: 99%
“…It is found that Co(II) phthalocyanines can transfer oxygen from various oxygen donors to alkanes, alkenes, phenols and thiols in the several studies [11e22]. Condensed aromatic compounds containing naphthalene derivatives are effective functional groups in photoemission studies [23,24]. Thus, in this paper we have aimed to synthesize a new class of cobalt phthalocyanines bearing 4-{2-(1-Naphthyloxy)-1-[(1-naphthyloxy)methyl]ethoxy}, 4-{2-(1-Naphthy loxy)-1-[(2-naphthyloxy)methyl]ethoxy} groups on the substitue nts.…”
Section: Introductionmentioning
confidence: 99%